Wind increases leaf water use efficiency. (5th February 2016) - Schymanski, Stanislaus J.; Or, Dani
Abstract: A widespread perception is that, with increasing wind speed, transpiration from plant leaves increases. However, evidence suggests that increasing wind speed enhances carbon dioxide (CO2 ) uptake while reducing transpiration because of more efficient convective cooling (under high solar radiation loads). We provide theoretical and experimental evidence that leaf water use efficiency (WUE, carbon uptake per water transpired) commonly increases with increasing wind speed, thus improving plants' ability to conserve water during photosynthesis. Our leaf‐scale analysis suggests that the observed global decrease in near‐surface wind speeds could have reduced WUE at a magnitude similar to the increase in WUE attributed to global rise in atmospheric CO2 concentrations. However, there is indication that the effect of long‐term trends in wind speed on leaf gas exchange may be compensated for by the concurrent reduction in mean leaf sizes. These unintuitive feedbacks between wind, leaf size and water use efficiency call for re‐evaluation of the role of wind in plant water relations and potential re‐interpretation of temporal and geographic trends in leaf sizes. Abstract : The study establishes theoretically and experimentally that, contrary to common expectations, wind increases leaf water use efficiency (WUE) under a wide range of environmental conditions. The increase reflects improved cooling efficiency by sensible heat and improved CO2 uptake (both controlled by boundary layer conductance). Results suggest that the potential influence of global stilling on WUE is of similar magnitude but acts in opposite direction to the effect of rising atmospheric CO2 concentrations. Additionally, reported decreases in leaf sizes over time are consistent with plant compensation for decreasing trends in wind speed that highlight the ecological significance of global stilling for leaf gas exchange. The results suggest that wind speed affects leaf WUE at the short time‐scale and leaf sizes at the long time‐scale.